Disproportionate burden of coronavirus disease 2019 among racial minorities and those in congregate settings among a large cohort of people with HIV. (1st October 2020) - Meyerowitz, Eric A.; Kim, Arthur Y.; Ard, Kevin L.; Basgoz, Nesli; Chu, Jacqueline T.; Hurtado, Rocio M.; Lee, Catherine K.; He, Wei; Minukas, Theresa; Nelson, Sandra; Ojikutu, Bisola O.; Robbins, Greg; et al.
Abstract : Background: Many people living with HIV (PLWH) have comorbidities which are risk factors for severe coronavirus disease 2019 (COVID-19) or have exposures that may lead to acquisition of severe acute respiratory distress syndrome coronavirus 2. There are few studies, however, on the demographics, comorbidities, clinical presentation, or outcomes of COVID-19 in people with HIV. Objective: To evaluate risk factors, clinical manifestations, and outcomes in a large cohort of PLWH with COVID-19. Methods: We systematically identified all PLWH who were diagnosed with COVID-19 at a large hospital from 3 March to 26 April 2020 during an outbreak in Massachusetts. We analyzed each of the cases to extract information including demographics, medical comorbidities, clinical presentation, and illness course after COVID-19 diagnosis. Results: We describe a cohort of 36 PLWH with confirmed COVID-19 and another 11 patients with probable COVID-19. Almost 85% of PLWH with confirmed COVID-19 had a comorbidity associated with severe disease, including obesity, cardiovascular disease, or hypertension. Approximately 77% of PLWH with COVID-19 were non-Hispanic Black or Latinx whereas only 40% of the PLWH in our clinic were Black or Latinx. Nearly half of PLWH with COVID-19 had exposure to congregate settings. In addition to people with confirmed COVID-19, we identified another 11 individuals with probable COVID-19, almost all of whom had negative PCR testing. Conclusion: In the largest cohort to date of PLWH and confirmed COVID-19, almost all had a comorbidity associated with severe disease, highlighting the importance of non-HIV risk factors in this population. The racial disparities and frequent link to congregate settings in PLWH and COVID-19 need to be explored urgently.